HGG-11. HIGH-GRADE GLIOMAS IN ADOLESCENTS AND YOUNG ADULTS HIGHLIGHT HISTOMOLECULAR DIFFERENCES WITH THEIR ADULT AND PAEDIATRIC COUNTERPARTS. (4th December 2020) - Roux, Alexandre; Pallud, Johan; Saffroy, Raphaël; Edjlali-Goujon, Myriam; Debily, Marie-Anne; Boddaert, Nathalie; Sanson, Marc; Puget, Stéphanie; Knafo, Steven; Adam, Clovis; Faillot, Thierry; Cazals-Hatem, Dominique; et al.
Abstract: BACKGROUND: Considering that paediatric high-grade gliomas (HGGs) are biologically distinct from their adult counterparts, the objective of this study was to define the landscape of HGGs in adolescents and young adults (AYAs). METHODS: We performed a multicentric retrospective study of 112 AYAs from adult and paediatric Ile-de-France neurosurgical units, treated between 1998 and 2013 to analyse their clinicoradiological and histomolecular profiles. The inclusion criteria were age between 15 and 25-years, histopathological HGG diagnosis, available clinical data, pre-operative and follow-up MRI. MRI and tumoral samples were centrally reviewed. Immunohistochemistry and complementary molecular techniques such as targeted/next generation sequencing, whole exome sequencing and DNA-methylation analyses were performed to achieve an integrated diagnosis according to the 2016 WHO classification. RESULTS: Based on 80 documented AYA patients, HGGs constitute heterogeneous clinicopathological and molecular groups, with a predominant representation of paediatric-subtypes (Histone H3-mutants, 40%) but also adult-subtypes ( IDH -mutants, 28%) characterized by the rarity of oligodendrogliomas, IDH -mutant and 1p/19q co-deleted and the relative high frequency of "rare adult IDH mutations" (20%). H3G34-mutants (14%) represent the most specific subgroup in AYAs. In the H3K27-mutant subgroup, the non-brainstem diffuse midline gliomas are more frequent (66.7%) than diffuse intrinsic pontine gliomas (23.8%), contrary to children. We found that WHO grade has no prognostic value, but molecular subgrouping has major prognostic importance. CONCLUSIONS: HGGs in AYAs could benefit from a more personalized neuro-oncological management, driven by molecular subtyping rather than age group. Collaborative efforts are needed from paediatric and adult neuro-oncology teams to improve the management of HGGs in AYAs.